The Role of Mirena (Intra-uterine progestogens), Other than Contraceptive benefits: Current Concepts and Practices (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Mirena is a long acting intrauterine hormone-releasing (LNG-IUS) contraceptive system with a flexible plastic T-shaped frame bearing a levonorgestrel(LNG)- containing cylinder which releases small doses levonorgestrel into the uterine cavity after insertion with maximum effect on the endometrium and minimum progestogenic side-effect. LNG causes thinning of the endometrium, atrophy of the endometrial glands and decidualisation of the endometrial stroma. The most common side-effect of LNG-IUS is unscheduled vaginal bleeding in the first 3 months, so proper counseling is needed. In some cases functional ovarian cysts may occur which are relatively small, symptomless and resolved spontaneously within a short time.Mirena is now licensed for the treatment of menorrhagia in UK because it reduces 97% of blood loss in 12 months uses. It is also an effective progestogenic endometrial protection in women with Hormone replacement therapy. There are conflicting evidence of LNG-IUS in the management of Fibroids uterus but it reduces fibroid related menstrual blood losses. It has also some beneficial effect in endometriosis and adenomyosis by reducing pain and blood loss. The LNG-IUS also reduces endometrial hyperplasia and may take place in the treatment of eartly endometrial cancer in some cases. The rate of ectopic pregnancy and pelvic inflammatory diseases are reduced in Mirena users compared with IUCD users.Keywords: Mirena; Intrauterine progestogens; Noncontraceptive; LNG-IUS DOI: 10.3329/jbcps.v28i3.6511J Bangladesh Coll Phys Surg 2010; 28: 167-173